Ionizing Radiation-inducible Apoptosis in the Absence of p53 Linked to Transcription Factor EGR-1 - Mansoor Ahmed; Stephen F. Sells; Kolaparthi Venkatasubbarao; Sana M. Fruitwala; Sumathi Muthukkumar; Cindy Harp; Mohammed Mohiuddin; Vivek M. Rangnekar (1997)
The tumor suppressor protein p53 is a pivotal regulator of apoptosis, and prostate cancer cells that lack p53 protein are moderately resistant to apoptotic death by ionizing radiation. Genes encoding the transcription factor early growth response-1 (EGR-1) and cytokine tumor necrosis factor-α (TNF-α) were induced upon irradiation of prostate cancer cells, and inhibition of EGR-1 function resulted in abrogation of both TNF-α induction and apoptosis. Induction of the TNF-α gene by ionizing radiation and EGR-1 was mediated via a GC-rich EGR-1-binding motif in the TNF-α promoter. Because TNF-α induces apoptosis in prostate cancer cells, these findings suggest that, in the absence of p53, ionizing radiation-inducible apoptosis is mediated by EGR-1 via TNF-α transactivation.